Design and Fabrication of Adventure Bike Water Distillator and Kettle - Ajay Deepak M. K.; Arul N.; Ragul R. K.; Dharrshan E.; Manoj M. (Journal of Electronic Design Engineering, 2020)
Travelling has become more popular today as a hobby and passion for many people. There are many problem faced by bikers in a long adventure road trips. One of the main problems is lack of availability of clean water. The main objective of this project is to utilize the heat from exhaust bend pipe to make the unclean water into drinkable one. This can also reduce the heat radiation of the engine so that the driver gets comfortability in drive since it used the heat generated from the side bend pipe of an exhaust system.